Theological Reflections on Environmental Justice: Christian and Islamic Perspectives on Stewardship and Creation Care in Indonesia (Indonesian Theological Justice Review, 2025)
Environmental justice is increasingly recognized as a critical issue in Indonesia, where ecological degradation, deforestation, and pollution disproportionately affect marginalized communities. This paper provides a comparative study of Christian and Islamic theological perspectives on environmental stewardship and creation care in Indonesia. The research explores how religious teachings from both faiths advocate for a responsible and sustainable relationship with the natural world. In Islam, the concept of khalifah (stewardship) and the Qur'anic imperative to protect the Earth are key theological principles that frame ecological responsibility. Similarly, Christian theology emphasizes the concept of creation care, drawing from biblical teachings about humans’ role as caretakers of God's creation. By examining how these religious teachings inform environmental activism and policy advocacy, the paper highlights the intersection of faith and environmental justice in Indonesia. The study evaluates the role of religious leaders, faith-based organizations, and communities in promoting environmental sustainability through advocacy, education, and direct action. Ultimately, it argues that theological reflections on environmental justice can be instrumental in addressing Indonesia’s environmental crises, providing both moral and practical guidance for creating more sustainable policies and practices.